2000
DOI: 10.1063/1.371867
|View full text |Cite
|
Sign up to set email alerts
|

Temperature behavior of multiple tunnel junction devices based on disordered dot arrays

Abstract: Nanometer-sized multijunction arrays are expected to exhibit a large Coulomb blockade effect. However, up to now, only highly disordered arrays can be fabricated. In this article, we evaluate the consequences of disorder on the dispersion of the device characteristics. We show that, as observed for regular arrays, the threshold voltage Vth increases with the length of the multijunction array. At very low temperature, the Vth dispersion is small. Conversely, at higher temperature, a large dispersion in Vth is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
37
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 18 publications
4
37
0
Order By: Relevance
“…Monte Carlo simulations have been used to study the effects of certain types of disorder on the conductance in one-dimensional ͑1D͒ and 2D nanoparticle arrays. [6][7][8][9][10] Disorder was taken into account in the form of variations in particle size, capacitative coupling between particles, and offset charges. Unfortunately, these calculations can only be applied to relatively small particle assemblies which poorly resemble a real nanoparticle film.…”
Section: Introductionmentioning
confidence: 99%
“…Monte Carlo simulations have been used to study the effects of certain types of disorder on the conductance in one-dimensional ͑1D͒ and 2D nanoparticle arrays. [6][7][8][9][10] Disorder was taken into account in the form of variations in particle size, capacitative coupling between particles, and offset charges. Unfortunately, these calculations can only be applied to relatively small particle assemblies which poorly resemble a real nanoparticle film.…”
Section: Introductionmentioning
confidence: 99%
“…For the disordered arrays the threshold also decreases linearly at low T. Decreases in the threshold with increasing temperature have also been observed in previous experiments on disordered arrays. 12,13,[15][16][17] In both the ordered and disordered arrays, for higher temperatures the threshold is lost and the nonlinear scaling of the I-V curve disappears and is replaced by linear behavior. Other experiments on ordered arrays have also found that temperature only weakly affects the shape of the I-V curves.…”
Section: Introductionmentioning
confidence: 99%
“…6,9 Previous simulations have been limited to Tϭ0, 1,4 or have considered only very small arrays. 17,18 Another type of perturbation that has recently been considered in experiments on highly resistive samples is the application of a sudden dc drive. 19 The application of a dc voltage that is below the conduction threshold voltage produces a current response that shows a two stage decay.…”
Section: Introductionmentioning
confidence: 99%
“…However, the arrays are not ordered in general. Junction parameters, including tunnel resistance R T and capacitance C, were largely dispersed [12]. On the other hand, a one-dimensional (1D) array of tunnel junctions will only work when every junction is functioning properly.…”
Section: Introductionmentioning
confidence: 99%